2004
DOI: 10.1242/jeb.00849
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense of an opilionid (Acanthopachylus aculeatus)

Abstract: SUMMARY The opilionid Acanthopachylus aculeatus was shown to produce a defensive secretion containing quinones (2,3-dimethyl-1,4-benzoquinone,2,5-dimethyl-1,4-benzoquinone and 2,3,5-trimethyl-1,4-benzoquinone),confirming the findings reported nearly a half century ago in a classic study. The mechanism by which the opilionid puts the secretion to use is described. When disturbed, the animal regurgitates enteric fluid, which it conveys by intercoxal clefts to the anterolateral corners of the carap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 14 publications
2
45
1
2
Order By: Relevance
“…The occurrence of alkylated 1,4-benzoquinones in G. longipes is chemotaxonomically in agreement with the constitution of the defensive secretions previously reported for other Gonyleptidae (Estable et al, 1955;Fieser and Ardao, 1956;Roach et al, 1980;Acosta et al, 1993;Eisner et al, 2004), including congeneric species, such as Goniosoma spelaeum (Gnaspini and Cavalheiro, 1998). The derivative 2,3-dimethyl-1,4-benzoquinone has been already identified in other harvestman species belonging to the families Cosmetidae, Gonyleptidae, and Manaosbiidae (Estable et al, 1955;Fieser and Ardao, 1956;Eisner et al, 1977Eisner et al, , 2004Roach et al, 1980;Acosta et al, 1993), but this is the first report of 2-ethyl-3-methyl-1,4-benzoquinone as a natural product. Moreover, the use of bidimensional nuclear magnetic resonance spectroscopy and high-resolution mass spectrometry is reported for the first time for chemical characterization of substances from harvestmen, providing additional protocols for studies of scent secretions in the group.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The occurrence of alkylated 1,4-benzoquinones in G. longipes is chemotaxonomically in agreement with the constitution of the defensive secretions previously reported for other Gonyleptidae (Estable et al, 1955;Fieser and Ardao, 1956;Roach et al, 1980;Acosta et al, 1993;Eisner et al, 2004), including congeneric species, such as Goniosoma spelaeum (Gnaspini and Cavalheiro, 1998). The derivative 2,3-dimethyl-1,4-benzoquinone has been already identified in other harvestman species belonging to the families Cosmetidae, Gonyleptidae, and Manaosbiidae (Estable et al, 1955;Fieser and Ardao, 1956;Eisner et al, 1977Eisner et al, , 2004Roach et al, 1980;Acosta et al, 1993), but this is the first report of 2-ethyl-3-methyl-1,4-benzoquinone as a natural product. Moreover, the use of bidimensional nuclear magnetic resonance spectroscopy and high-resolution mass spectrometry is reported for the first time for chemical characterization of substances from harvestmen, providing additional protocols for studies of scent secretions in the group.…”
Section: Discussionsupporting
confidence: 89%
“…The caustic, irritating, and odoriferous properties of these substances may cause invertebrate predators to desist from the attack and to perform vigorous cleaning activities (Eisner and Meinwald, 1966). Recently, Eisner et al (2004) showed that the secretion of the gonyleptid harvestman A. aculeatus (Pachylinae) was an effective deterrent against the ant Formica exsectoides. Using a different protocol, we here demonstrate that secretions containing the 1,4-benzoquinones produced by the gonyleptid G. longipes (Goniosomatinae) effectively repel five species of ants belonging to three subfamilies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations